Engineered ACE2 receptor therapy overcomes mutational escape of SARS-CoV-2 - Yusuke Higuchi (Nature Portfolio, 2021)
Hoshino et al., engineer a human virus receptor, hACE2, and demonstrate its potential for overcoming SARS-CoV-2 mutations that otherwise hinder therapeutic interventions. Overall, the data provide insights in to the therapeutic potential of engineered receptors.